The Relationship between Domestic Violence and Reproductive Health and Family Planning Services in Bolivia, 2003. - Pinto Aguirre, Guido (2010)
The main purpose of this paper is to understand the relationship existing between Gender-Based Violence (GVB) and the Use of Reproductive Health and Family Planning services. To carry out this task, we use multivariate logit regression models to explore the direction and strength of the relationship, using a population-based sample for Bolivian women during 2003-2004. Results show a strong, negative and significant relationship between GVB and use of RH/FP services at the population-level, after adjusting for respondent's and partner's individual and household characteristics. That is, GBV is strongly and significantly associated with the use of RH/FP services, in a way that women experiencing domestic violence are less likely to use those services.